2002
DOI: 10.1051/0004-6361:20020104
|View full text |Cite
|
Sign up to set email alerts
|

The complex X-ray spectrum of the supersoft source

Abstract: Abstract. We present the X-ray spectrum of MR Vel / RX J0925.7−4758, obtained with the Medium Energy Grating spectrometer of the Chandra X-ray Telescope. The simplest models used by earlier authors, stellar atmospheres in combination with a thermal plasma in collisional ionization equilibrium, cannot explain the spectrum. Neither does a photo-ionized plasma. We identify P Cygni profiles of Fe XVII and O VIII, from which we conclude that these lines arise in a wind. We conclude that major uncertainty exists abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Lanz et al 2005, Rajoelimanana et al 2013) has shown that they indeed consist of a hot WD in a close orbit with a non-degenerate donor, where hydrogen accreted from the donor, at roughly the above rates, burns more-or-less stably into helium on the WD surface (van den Heuvel et al 1992). However, not all supersoft source spectra are easily interpreted in this way, as some show P-Cygni profiles indicative of a wind rather than a WD atmosphere (Bearda et al 2002). Because of interstellar absorption of their soft X-ray spectrum, supersoft sources have been discovered mainly in external nearby galaxies.…”
Section: Recurrent Novaementioning
confidence: 99%
“…Lanz et al 2005, Rajoelimanana et al 2013) has shown that they indeed consist of a hot WD in a close orbit with a non-degenerate donor, where hydrogen accreted from the donor, at roughly the above rates, burns more-or-less stably into helium on the WD surface (van den Heuvel et al 1992). However, not all supersoft source spectra are easily interpreted in this way, as some show P-Cygni profiles indicative of a wind rather than a WD atmosphere (Bearda et al 2002). Because of interstellar absorption of their soft X-ray spectrum, supersoft sources have been discovered mainly in external nearby galaxies.…”
Section: Recurrent Novaementioning
confidence: 99%
“…The blue edge of the mean Ly α O  P Cygni profile shown in Fig. 7 is at velocities close to 2000 km s −1 slightly larger than the 1500 km s −1 derived by Bearda et al (2002), but much less than that of the transient collimated wind or jet discovered by Motch (1998).…”
Section: Overall Spectrummentioning
confidence: 52%
“…Figure 8 shows the ratio of the high to low EPIC pn spectra plotted for the merged revolutions 187 and 188 data. Although the NLTE model atmosphere of Bearda et al (2002) does not satisfactorily fit the EPIC pn spectrum, it provides a better representation than black body spectra and can be used to estimate the expected distortion of the energy distribution if it was only due to photoelectric absorption. In the 0.5-1.0 keV range the high to low ratio of 1.277 can be mimicked by a change from N H = 1.485 × 10 22 to 1.540 × 10 22 cm −2 , keeping all other parameters constant.…”
Section: Variability With Orbital Phases and Flux Levelmentioning
confidence: 99%
See 2 more Smart Citations